INTRODUCTION TO SPATIAL FIGURES IN PRIMARY GRADES (Educator Insights: Journal of Teaching Theory and Practice, 2026)
In this article, it is given about useful ways of utilizing geometric materials with primary school pupils. In addition, practical works in this field are indicated.